Environmentally friendly pressure-sensitive adhesive, pressure-sensitive tape and preparation method thereof

By optimizing the components and preparation methods of pressure-sensitive adhesives, the existing pressure-sensitive adhesive tape is solved, and the problem of high peeling force, high-temperature weight-bearing long retention force and adhesion force to the surface of low-surface energy products is achieved, and an efficient and environmentally friendly adhesion effect is achieved, meeting the needs of the electronics industry and new energy vehicles.

CN119775928APending Publication Date: 2025-04-08DELSSON (XIAMEN) IND CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510007001.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-03
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

Existing pressure-sensitive tapes are difficult to meet the high peeling force, high-temperature weight-bearing long retention force and the adhesion force to the surface of low-surface energy products at the same time. Especially under the environmental protection requirements of no aromatic solvents, there are fewer commercial products.

Method used

By optimizing the components of the pressure-sensitive adhesive and its preparation method, an environmentally friendly pressure-sensitive adhesive with a solid content of 35%-50% and a viscosity of 5500-15500CPS is prepared using a combination of acrylate copolymer, tackifying resin, temperature-resistant additive, defoaming agent, antioxidant, diluent and curing agent.

Benefits of technology

It has achieved high peeling force, long-term high-temperature weight bearing holding force and good adhesion to the surface of low-surface energy products, and does not contain aromatic solvents, which meets the adhesion needs of the electronics industry and new energy vehicles and has made significant progress in environmental protection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119775928A_ABST
    Figure CN119775928A_ABST
Patent Text Reader

Abstract

The present invention discloses an environment-friendly pressure-sensitive adhesive, a pressure-sensitive tape and a preparation method thereof. The environment-friendly pressure-sensitive adhesive comprises the following components by mass fraction: 100 parts of acrylate copolymer, 8-20 parts of tackifying resin, 0-2 parts of temperature-resistant auxiliary agent, 0.5-1.5 parts of defoamer, 0.5-1 parts of antioxidant, 20-50 parts of diluent, and 0.6-1.5 parts of curing agent. Wherein the acrylate copolymer is obtained by in-situ synthesis of silylated acrylamide and IBOA, HEA, and 2-EHA. The pressure-sensitive tape obtained by coating the adhesive on a substrate has high peeling force, long sticking time under high temperature load conditions, and good adhesion to the surface of low surface energy products, which can meet the bonding requirements of high temperature environment, new energy vehicles, artificial intelligence sensors, etc. At the same time, the tape does not contain aromatic solvents during production, does not harm the human body and the environment, and has great progress in environmental protection.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of adhesives, and in particular to an environmentally friendly pressure-sensitive adhesive and a pressure-sensitive adhesive tape made from the adhesive. Background Art

[0002] Pressure-sensitive tape is made by coating pressure-sensitive adhesive on one or both sides of the substrate, drying it, and then covering it with an easy-to-peel release material and then aging it. High-strength pressure-sensitive tape has good resistance to rebound, warping, heat and temperature resistance. It also has strong adhesion and holding power. It has good adhesion to a variety of substrates, is easy to tear, and is clean to use; it has good adhesion to rough surfaces, oily surfaces, chemical fibers, kapok cloth and other materials. It is not only suitable for flat pasting, but also for arc pasting, and is suitable for pasting stamping, nameplates, and membrane switches; it can be used to fit logos, photos, envelopes, hooks, etc. It is also used in the shoemaking and leather industries; for bonding PP, PE, PU, ​​foam and other materials. The scope of use is very wide.

[0003] Industrial and electronic-grade tapes, such as those used for bonding on-board electronic displays, new energy vehicles, and various sensor components, need to be resistant to high temperatures, have high peeling force and retention force, maintain load-bearing capacity in high-temperature environments, and have a certain degree of adhesion to some materials with low surface energy. Especially for automotive and new energy products, the products are also required not to contain aromatic solvents. However, most of the current commercialized pressure-sensitive tape products are already difficult to simultaneously meet the three indicators of high peeling force, long retention force under high temperature loads, and adhesion to the surface of low-surface-energy products. Adding the requirement for environmentally friendly solvents, there are even fewer commercial products that can meet these requirements. Therefore, based on the urgent needs of reality, this case came into being. Summary of the invention

[0004] In order to overcome the above-mentioned defects of the prior art and meet the performance requirements of the electronics industry for pressure-sensitive adhesives to have high peeling force, long retention under high temperature and load, and adhesion to the surface of low surface energy products, the present invention optimizes the components and the preparation method thereof.

[0005] In order to achieve the purpose of the present invention, the technical scheme adopted by the present invention is: an environmentally friendly pressure-sensitive adhesive, which comprises the following components by weight: 100 parts of acrylate copolymer, 8-20 parts of tackifying resin, 0-2 parts of temperature-resistant auxiliary agent, 0.5-1.5 parts of defoaming agent, 0.5-1 parts of antioxidant, 20-50 parts of diluent, and 0.6-1.5 parts of curing agent; wherein the acrylate copolymer has a general formula as shown in structural formula (I), and is synthesized from four monomers of silylated acrylamide, IBOA, HEA and 2-EHA,

[0006]

[0007] Wherein, a, b, c and d in the structural formula I are independent of each other. The preferred environmentally friendly pressure-sensitive adhesive has a solid content of 35%-50% and a viscosity of 5500-15500 CPS.

[0008] Furthermore, the tackifying resin is at least one of rosin resin, hydrogenated rosin, terpene resin, and terpene phenol resin. Preferably, the softening point of the tackifying resin is 105°C-160°C. The diluent is a combination of at least one or more of ethyl acetate, propylene glycol methyl ether, propylene glycol methyl ether carbonate, and methyl cyclohexane. The curing agent is at least one of isocyanate or epoxy curing agent; the temperature-resistant auxiliary agent is a propylene glycol methyl ether solution containing 5% aluminum acetylacetonate.

[0009] The present invention also provides a method for preparing an environmentally friendly pressure-sensitive adhesive, comprising the following steps:

[0010] Step 1, preparation of acrylate copolymer: using benzoyl peroxide as initiator and ethyl acetate as solvent, adding silylated acrylamide, IBOA, HEA and 2-EHA four monomers in a weight ratio of 10:20:15:65, and synthesizing in situ by solution polymerization; reaction temperature 80°C-85°C, reaction time 6-8 hours; wherein the solid content of the acrylate copolymer solution is controlled at 40%, and the amount of initiator is controlled at 0.4%-0.6% of the total monomers;

[0011] Step 2: Mix and stir the acrylic acid ester copolymer with a tackifying resin, a temperature-resistant auxiliary agent, a defoaming agent, an antioxidant, a diluent, and a curing agent in parts by mass to obtain a product.

[0012] The silanized acrylamide used in step 1 has the general formula shown in structural formula (II),

[0013]

[0014] Furthermore, the preparation of silylated acrylamide containing the general formula as shown in structural formula (II) comprises the following steps: A) activating silica gel, placing silica gel in a hydrochloric acid solution, subjecting it to ultrasonic treatment and heating under reflux for activation; B) silylation of the activated silica gel with aminopropyltriethoxysilane to obtain aminopropyl silica gel; and C) reacting aminopropyl silica gel with acryloyl chloride to obtain silylated acrylamide.

[0015] Further, in a more specific process of step 1, the monomer and the solvent are loaded into a reaction container, and when the temperature reaches 80°C-85°C, half of the initiator dissolved in ethyl acetate is continuously added within 1 hour; after 1 hour, one quarter of the initiator is added dropwise within 30 minutes; after another 1 hour, the rest of the initiator is added dropwise within 30 minutes; the reaction is continued for 2 hours to obtain the acrylic ester copolymer.

[0016] The invention provides a pressure-sensitive adhesive tape, comprising a substrate and a dry adhesive layer of an environmentally friendly pressure-sensitive adhesive prepared by the invention, wherein the environmentally friendly pressure-sensitive adhesive is coated on one side or both sides of the substrate; the substrate is PET, cotton paper or non-woven fabric, and has a thickness of 12-50 μm; and the dry adhesive layer of the environmentally friendly pressure-sensitive adhesive has a thickness of 25-100 μm.

[0017] Beneficial effects: The acrylate copolymer in the pressure-sensitive adhesive of the present invention is obtained by in-situ synthesis of silylated acrylamide and IBOA, HEA and 2-EHA monomers.

[0018] The pressure-sensitive adhesive tape obtained by coating the adhesive prepared by the method of the present invention on a substrate has high peeling force, long adhesion time under high temperature and load conditions, and good adhesion to the surface of low surface energy products, and the adhesive does not contain aromatic solvents. It can meet the bonding requirements of high temperature environments and new energy vehicles, artificial intelligence sensors, etc. At the same time, the tape does not contain aromatic solvents during the production process, has no harm to the human body and the environment, and has made great progress in environmental protection.

[0019] The prepared pressure-sensitive adhesive tape product is stable and has excellent performance, and is suitable for large-scale promotion. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 This is a process for preparing silylated acrylamide in one embodiment.

[0021] Figure 2 The present invention is a synthesis of an acrylate copolymer in one embodiment.

[0022] Figure 3 This is one of the embodiments of the peel force testing process. DETAILED DESCRIPTION

[0023] In order to better understand the technical solution of the present invention, the embodiments of the present invention are described in detail below in conjunction with specific embodiments. It should be clear that the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0024] The terms used in the embodiments of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The singular forms of "a", "said" and "the" used in the embodiments of the present invention and the appended claims are also intended to include plural forms unless the context clearly indicates other meanings. The test materials used in the present invention are all common commercial products and can be purchased on the market.

[0025] An environmentally friendly pressure-sensitive adhesive is composed of an acrylic copolymer, a tackifying resin, a temperature-resistant additive, a defoaming agent, an antioxidant, a diluent, and a curing agent according to the following components. Calculated by mass:

[0026] Acrylate copolymer 100 parts

[0027] 8-20 parts of tackifying resin

[0028] Heat resistant additive 0.5-2 parts

[0029] Defoamer 0.5-1.5 parts

[0030] 0.5-1 part antioxidant

[0031] 20-50 parts of diluent

[0032] Curing agent 0.6-1.5 parts

[0033] The solid content of the pressure-sensitive adhesive is 35%-50% and the viscosity is 5500-15500 CPS.

[0034] Furthermore, the acrylic acid ester copolymer component contains structural units of the following structural formula (I):

[0035]

[0036] The tackifying resin is at least one of rosin resin, hydrogenated rosin, terpene resin and terpene phenol resin, which can be purchased from the market. The heat-resistant auxiliary agent is a propylene glycol methyl ether solution containing 5% aluminum acetylacetonate.

[0037] The diluent is a mixture of at least one or more of ethyl acetate, propylene glycol methyl ether, propylene glycol methyl ether carbonate and methyl cyclohexane in a certain proportion.

[0038] The curing agent is at least one of an isocyanate or an epoxy curing agent. The amount of the curing agent used depends on the specific application requirements and the system. Generally speaking, if the amount of the curing agent is too much, it will cause the acrylic oligomer to self-crosslink; on the contrary, if the amount of the curing agent is too little, the polar functional groups of the tackifying resin will remain, which will cause the viscosity of the system to decrease.

[0039] It should be noted that the defoamer, antioxidant and curing agent used must be miscible with the entire system, otherwise stratification will occur.

[0040] The present invention also provides the preparation steps of the environmentally friendly pressure-sensitive adhesive, which are specifically as follows:

[0041] Step 1, preparation of silanized acrylamide

[0042] Silylated acrylamide has the general formula shown in structural formula (II),

[0043]

[0044] The preparation of silylated acrylamide comprises the following steps: A) activating silica gel, placing the silica gel in a hydrochloric acid solution, subjecting it to ultrasonic treatment and heating under reflux for activation; B) silylation of the activated silica gel with aminopropyltriethoxysilane to obtain aminopropyl silica gel; and C) reacting aminopropyl silica gel with acryloyl chloride to obtain silylated acrylamide.

[0045] Step 2, Preparation of Acrylate Copolymer

[0046] The silylated acrylamide obtained in step 1 and four monomers, namely, isobornyl acrylate (IBOA), hydroxyethyl acrylate (HEA), and 2-ethylhexyl acrylate (2-EHA), are synthesized in situ by solution polymerization. Ethyl acetate is used as solvent, benzoyl peroxide (BPO) is used as initiator, and the reaction is carried out at 80°C-85°C for 6-8 hours. Preferably, 65 parts of 2-EHA, 15 parts of HEA, 20 parts of IBOA, and 10 parts of silylated acrylamide are added by mass for synthesis. The reaction temperature of 80°C-85°C is summarized based on the research and development process. If the temperature exceeds the limit, BPO is prone to form explosive substances, increasing incomplete factors, and at the same time causing the product composition to become complicated.

[0047] In one preferred embodiment, the above monomers and solvent are added to a 1L four-necked round flask equipped with a mechanical stirring rod, a reflux condenser and a thermometer. When the temperature reaches 80°C, half of the initiator dissolved in ethyl acetate is continuously added within one hour; after one hour, one quarter of the initiator is added dropwise within 30 minutes; after another hour, the remaining initiator is added dropwise within 30 minutes; the reaction is continued for 2 hours to obtain the acrylate copolymer. The solid content of the acrylate copolymer solution is controlled at 40%, and the amount of initiator is controlled at 0.4%-0.6% of the total monomers.

[0048] Step 3, mixing and stirring the prepared acrylic ester copolymer with a tackifying resin, a temperature-resistant auxiliary agent, a defoaming agent, an antioxidant, a diluent, and a curing agent according to parts by mass to obtain a product.

[0049] Step 1 In one preferred embodiment, the preparation of silanized acrylamide is as follows:

[0050] A) Activated silica gel: add 100 g silica gel and 600 mL 6M hydrochloric acid into a 1500 mL three-necked bottle, treat with ultrasound for 30 min, reflux at 100° C. for 5 h, filter out the silica gel, wash with deionized water until neutral, dry under vacuum at 100° C. for 6 h, and place in a desiccator to cool for later use.

[0051] B) Preparation of aminopropyl silica gel: 100 g of the above activated silica gel, 500 mL of xylene and 100 mL of aminopropyltriethoxysilane were added to a 1500 mL three-necked bottle, refluxed at 130° C. for 8 h under nitrogen protection, filtered, washed with toluene, methanol and toluene in sequence, and then vacuum dried at 150° C. for 5 h to obtain aminopropyl silica gel.

[0052] C) To prepare silylated acrylamide, 50 g of aminopropyl silica gel, 10 mL of triethylamine, and 500 mL of toluene were added to a 1500 mL three-necked bottle, and 20 mL of acryloyl chloride was added dropwise at room temperature for reaction. After the reaction was completed, stirring was continued for 4 h. After the reaction was completed, the mixture was filtered out, washed with toluene, acetone, THF, and deionized water in sequence, and vacuum dried for use.

[0053] The present invention also provides a pressure-sensitive adhesive tape, which is obtained by coating the pressure-sensitive adhesive prepared by the present invention on one or both sides of a substrate, heating and drying in an oven, and then laminating with a release paper or a release film, rolling up, and aging. More specifically, the oven temperature is 100°C-120°C, the aging temperature is 60°C, and the aging time is 2 days. In a specific example, the substrate of the pressure-sensitive adhesive tape can be one of PET, cotton paper, and non-woven fabric; the thickness is 12-50 μm. The dry adhesive thickness of the pressure-sensitive adhesive tape is 25-100 μm.

[0054] According to the preparation steps of the aforementioned environmentally friendly pressure-sensitive adhesive, three groups of examples were prepared, each group having 5 combinations in different ratios.

[0055] The first group of embodiments, the component changes are shown in Table 1. The effect of the acrylate copolymer prepared by the present invention and the number of different tackifying resins on the performance of the pressure-sensitive adhesive was explored. The tackifying resin in this group of experiments is a rosin resin with a softening point of 105°C. The defoamer is TEGO Airex 900, the curing agent is Bayer L75, the antioxidant is BX AO 1135 of Dongguan Baoxu Chemical Technology Co., Ltd., the heat-resistant auxiliary agent is 5% aluminum acetylacetonate solution (preparation method: 5% aluminum acetylacetonate, 75% PGME, 20% acetylacetone), and the diluent is a composition of 25 parts of ethyl acetate and 10 parts of propylene glycol methyl ether.

[0056] Table 1 Matching of acrylate copolymer and tackifying resin content

[0057] Experiment No. 1-1 1-2 1-3 1-4 1-5 Acrylate copolymer 100 100 100 100 100 Tackifying resin 0 5 10 15 20 Heat resistant additives 0 0 0 0 0 Curing agent 0.8 0.8 0.8 0.8 0.8 Defoaming agent 0.5 0.5 0.5 0.5 0.5 Antioxidants 0.5 0.5 0.5 0.5 0.5 Thinner 35 35 35 35 35

[0058] Mix the components according to the proportions in Table 1 and stir with an electric mixer for 40 minutes. Apply the glue evenly on one side of the 25u PET film on a scraper-type coater, dry it in a 105°C oven for 3 minutes, control the thickness of the dry glue to 50 microns, and laminate it on a 25u single-sided release film and roll it up with a laminating roller. Use the same method to apply the glue on the other side of the 25u PET, tear off the release film on the second side, and roll it up. You can get a PET double-sided tape. Place the prepared PET double-sided tape roll in a 45°C oven, mature it for 72 hours, and test its performance.

[0059] Test method: The peel strength of the adhesive tape is tested according to the test method of GB / T 2792-2014. The adhesive tape retention is tested according to the test method of GB / T 4851-2014. The thickness of the adhesive tape is tested according to the test method of GB / T 7125-2014. Test conditions: The test temperature is 25°C, 50-55% RH, and the holding force is the test data with a 1000g weight hanging below. The peel force is the peel force on the steel plate in the 180-degree direction at room temperature for 20 minutes. Table 2 is the test results of the first group of embodiments.

[0060] Table 2 Test results of the first group of embodiments

[0061] Experiment No. Peel force (N / 25mm) Room temperature retention 80℃ holding power 1-1 13.52 9.5H 20min 1-2 17.87 17.5H 27.5min 1-3 19.66 37.5H 28min 1-4 22.42 >72H 32.5min 1-5 23.55 >72H 35min

[0062] From the above test, it can be seen that as the proportion of tackifying resin increases, the peel strength value of the tape of the same thickness continues to rise. When the proportion of tackifying resin reaches 15 parts (Examples 1-4), further increasing the proportion of tackifying resin does not have a significant effect on the increase in peel strength. At the same time, the holding power at room temperature is also significantly improved, but the holding power at 80°C is not significantly increased.

[0063] The second group of examples, the components of which are changed as shown in Table 3. The temperature resistance of the pressure-sensitive adhesive is further optimized for the first group of examples. On the basis of the first group of examples, a temperature-resistant additive is further added to optimize the temperature resistance of the pressure-sensitive adhesive tape. The acrylic copolymer, tackifying resin, curing agent, defoaming agent, antioxidant, and diluent are the same as those of the first group of examples.

[0064] Table 3 Optimization of temperature resistance of pressure-sensitive adhesive tape

[0065] Experiment No. 2-1 2-2 2-3 2-4 2-5 Acrylate copolymer 100 100 100 100 100 Tackifying resin 15 15 15 15 15 Heat resistant additives 0.4 0.6 0.8 1.0 1.5 Curing agent 0.8 0.8 0.8 0.8 0.8 Defoaming agent 0.5 0.5 0.5 0.5 0.5 Antioxidants 0.5 0.5 0.5 0.5 0.5 Thinner 35 35 35 35 35

[0066] The PET double-sided tape roll was made in the same manner as the first embodiment to test its performance. The heat-resistant additive was a propylene glycol methyl ether solution containing 5% aluminum acetylacetonate. The test method and test conditions were also the same as those of the first embodiment. Table 4 is the test results of the second embodiment.

[0067] Table 4 Test results of the second embodiment

[0068] Experiment No. Peel force (N / 25mm) Room temperature retention 80℃ holding power 2-1 12.52 22.5H 1h18min 2-2 14.87 45.3H 2H35min 2-3 15.66 >72H 3h16min 2-4 14.62 >72H 3H45min 2-5 13.55 >72H 1H15min

[0069] As the proportion of heat-resistant additive added increases, the initial adhesion of the tape deteriorates, the peeling force decreases rapidly, but the cohesive force increases, the holding force at room temperature becomes better, and the holding force at high temperature is also significantly improved. From a comprehensive comparison of the experimental results, Example 2-3 adds 0.8 parts of heat-resistant additive and has the best effect. However, due to the low softening point of the tackifying resin, the holding force in a high temperature environment cannot be maintained for a long enough time. Therefore, it is preliminarily determined that the use of a tackifying resin with a higher softening point can improve the high temperature resistance effect.

[0070] The third group of embodiments, the matching of tackifying resins with different softening points and acrylate copolymers. The heat-resistant additive is a propylene glycol methyl ether solution containing 5% aluminum acetylacetonate. The acrylate copolymer, heat-resistant additive, curing agent, defoaming agent, antioxidant, and diluent are the same as the first group of embodiments. The PET double-sided tape roll is made with the first group of embodiments to test its performance. The test method and test conditions are also the same as the first group of embodiments. Table 6 is the test results of the third group of embodiments.

[0071] Table 5 Matching of tackifying resins with different softening points and acrylate copolymers

[0072]

[0073] Among them, the tackifying resin used in Example 3-1 is GRANOLITE P118 (softening point 118°C, TG 74°C), the tackifying resin used in Example 3-2 is DERTOPOLINE P125 (softening point 128°C, TG 80°C), the tackifying resin used in Example 3-3 is POLYGRAL 140 (softening point 138°C, TG 98°C), the tackifying resin used in Example 3-4 is DERTOPHENE 1510 (softening point 149°C, TG 105°C), and the tackifying resin used in Example 3-5 is DERTOPHENET160 (softening point 160°C, TG 110°C).

[0074] Table 6 Test data of the third embodiment

[0075] Experiment No. Peel force (N / 25mm) Room temperature retention 80℃ holding power 3-1 21.22 >72H 7H 35min 3-2 23.87 >72H 19H 22min 3-3 25.15 >72H 45H 15min 3-4 24.22 >72H >72H 3-5 21.55 >72H 5H 38min

[0076] As the softening point and TG temperature of the tackifying resin increase, the high temperature resistance effect becomes better, but if it is too high, the initial adhesion performance of the product will further decrease, and the bonding strength to the steel plate will become worse, resulting in a decrease in the sustained adhesion effect. Figure 3 The results of the peeling force test of Examples 3-4 are shown. To avoid repetition, only one of the examples is described.

[0077] Table 7 Peel force test of Example 3-4

[0078]

[0079] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. An environmentally friendly pressure-sensitive adhesive, characterized in that: The composition comprises the following components by weight: 100 parts of acrylate copolymer, 8-20 parts of tackifying resin, 0-2 parts of heat-resistant additive, 0.5-1.5 parts of defoaming agent, 0.5-1 parts of antioxidant, 20-50 parts of diluent and 0.6-1.5 parts of curing agent; wherein the acrylate copolymer is synthesized from four monomers of silanized acrylamide, IBOA, HEA and 2-EHA, and contains the general formula shown in structural formula (I), Wherein, a, b, c, and d in structural formula (I) are independent of each other.

2. The environmentally friendly pressure-sensitive adhesive according to claim 1, characterized in that Its solid content is 35%-50% and its viscosity is 5500-15500 CPS.

3. The environmentally friendly pressure-sensitive adhesive according to claim 1, characterized in that: The tackifying resin is at least one of rosin resin, hydrogenated rosin, terpene resin and terpene phenol resin.

4. The environmentally friendly pressure-sensitive adhesive according to claim 3, characterized in that: The softening point of the tackifying resin is 105°C-160°C.

5. The environmentally friendly pressure-sensitive adhesive according to claim 1, characterized in that: The curing agent is at least one of isocyanate or epoxy curing agent; the heat-resistant auxiliary agent is a propylene glycol methyl ether solution containing 5% aluminum acetylacetonate.

6. A method for preparing the environmentally friendly pressure-sensitive adhesive according to any one of claims 1 to 5, characterized in that: The following steps are included: Step 1, preparation of acrylate copolymer: using benzoyl peroxide as initiator and ethyl acetate as solvent, adding silylated acrylamide, IBOA, HEA and 2-EHA four monomers in a weight ratio of 10:20:15:65, and synthesizing in situ by solution polymerization; reaction temperature 80°C-85°C, reaction time 6-8 hours; wherein the solid content of the acrylate copolymer solution is controlled at 40%, and the amount of initiator is controlled at 0.4%-0.6% of the total monomers; Step 2: Mix and stir the acrylic acid ester copolymer with a tackifying resin, a temperature-resistant auxiliary agent, a defoaming agent, an antioxidant, a diluent, and a curing agent in parts by mass to obtain a product.

7. The preparation method according to claim 6, characterized in that: The silylated acrylamide has the general formula shown in structural formula (II), 8. The preparation method according to claim 7, characterized in that: The preparation of the silylated acrylamide comprises the following steps: A) activating silica gel by placing the silica gel in a hydrochloric acid solution, subjecting it to ultrasonic treatment and heating under reflux for activation; B) silylation of the activated silica gel with aminopropyltriethoxysilane to obtain aminopropyl silica gel; and C) reacting aminopropyl silica gel with acryloyl chloride to obtain silylated acrylamide.

9. The preparation method according to claim 6, characterized in that: The more specific process of step 1 is to load the monomer and the solvent into a reaction container, and when the temperature reaches 80°C-85°C, continuously add half of the initiator dissolved in ethyl acetate within 1 hour; after 1 hour, add another quarter of the initiator within 30 minutes; after another 1 hour, add the rest of the initiator within 30 minutes; continue the reaction for 2 hours to obtain the acrylic ester copolymer.

10. A pressure-sensitive adhesive tape, characterized in that: It comprises a substrate and a dry adhesive layer of the environmentally friendly pressure-sensitive adhesive according to any one of claims 1 to 5, wherein the environmentally friendly pressure-sensitive adhesive is coated on one side or both sides of the substrate; the substrate is PET, cotton paper or non-woven fabric, and has a thickness of 12-50 μm; the thickness of the dry adhesive layer of the environmentally friendly pressure-sensitive adhesive is 25-100 μm.